IMPLEMENTATION OF WASTE MANAGEMENT POLICY - Nusi, Marten; Arman; Prahara, Sandi; Razak, Darmawaty Abd (International Peneliti Ekonomi, Sosial dan Teknologi, 2025)
The purpose of this study is to analyze the process of implementing the policy implementation of Gorontalo City regional regulation no. 12 of 2017 concerning Waste Management in Hulonthalangi District. This research was conducted by a qualitative method, the data collection techniques used were using interviews, observations and documentation. The data analysis technique is interactive data analysis. The results of the research as indicators of the success of policy implementation used in this study, both in terms of socialization, the availability of supporting facilities, and factual budget support are not available or can even be said to have received full attention from the Gorontalo City local government. As suggestions and recommendations that can be given by researchers as part of constructive things, the importance of education that is continuously carried out massively by local governments, the need for full penetration from local governments on the availability of supporting facilities and infrastructure, the availability of sufficient budgets as part of policy financing also needs to be prepared by local governments, communication and coordination across sectors, addition to temporary waste collection points at each point in each sub-district in the Gorontalo City area.